Changing of an Airy pulse form due to re-reflections inside a dielectric layer - Kuryzheva, O. V.; Nerukh, A. G. (YSF, 2016)
A problem of Airy pulse transformation by a plane-parallel layer is considered. A problem formulation is equivalent to a case of permittivity sharp change in a dielectric layer at zero moment of time. It allows to use the resolvent method for solution of the Volterra integral equation describing this phenomenon. It is shown a virtual structure of a pulse field inside the layer. Influence of a number of pulse re-reflections from the layer boundaries on a form of a primary pulse is analyzed.
Keywords: airy pulse; layer; re-realection; electromagnetic field